The challenges of German-English literary translation: an exploration of Franz Kafka's Das Urteil (The Judgment) and Die Verwandlung (The Metamorphosis) - Thabane, Mathaabe (Rhodes University, Faculty of Humanities, School of Languages, 2016)
This thesis conducts a study of literary translation using selected texts by Franz Kafka as translated from German into English in the mid-twentieth century and in the early twenty-first century. This study entails a three-fold orientation, namely: to show the extent of the impact of socio-historical, political and cultural factors on both the translation process and translation product; secondly, it demonstrates the fact that a merging of theoretical principles and practical methods is necessary and possible for the study of literary translations; thirdly, it answers the questions of why the same literary works continue to be retranslated and why every generation of Kafka scholars and readers will need their own translations of his works. This research, furthermore, proposes that the position of literary translation should be elevated since this kind of translation can reveal more about the cultural and linguistic intricacies of the translation process. Seeking to contribute to the broader framework of the translation studies discipline, this thesis also makes a case for translators to reveal their translation process, in the form of notes or prefaces, in order to allow for informed studies of translations. Finally, the research at hand proposes some considerations for further study into literary translations and shows new trends in the sub-field of literary translation which will undoubtedly shift its current nature and call for theoretical and practical applications for more classes of languages.
Keywords: Uncatalogued